Influence of bariatric surgery on the peripheral blood immune system of female patients with morbid obesity revealed by high-dimensional mass cytometry - Gihring, Adrian; Gärtner, Fabian; Mayer, Laura; Roth, Aileen; Abdelrasoul, Hend; Kornmann, Marko; Elad, Leonard; Knippschild, Uwe (Frontiers in Immunology, 2023)
Introduction Obesity is associated with low-grade chronic inflammation, altered levels of adipocytokines, and impaired regulation of gastrointestinal hormones. Secreted, these factors exert immunostimulatory functions directly influencing peripheral immune cells. Methods In the realm of this study, we aimed to investigate the composition and activation status of peripheral blood immune cells in female patients with morbid obesity compared to lean controls using high-dimensional mass cytometry. Besides, we also assessed the influence of bariatric surgery with respect to its ability to reverse obesity-associated alterations within the first-year post-surgery. Results Patients with morbid obesity showed typical signs of chronic inflammation characterized by increased levels of CRP and fibrinogen. Apart from that, metabolic alterations were characterized by increased levels of leptin and resistin as well as decreased levels of adiponectin and ghrelin compared to the healthy control population. All these however, except for ghrelin levels, rapidly normalized after surgery with regard to control levels. Furthermore, we found an increased population of monocytic CD14+, HLA-DR-, CD11b+, CXCR3+ cells in patients with morbid obesity and an overall reduction of the HLA-DR monocytic expression compared to the control population. Although CD14+, HLA-DR-, CD11b+, CXCR3+ decreased after surgery, HLA-DR expression did not recover within 9 – 11 months post-surgery. Moreover, compared to the control population, patients with morbid obesity showed a perturbed CD4+ T cell compartment, characterized by a strongly elevated CD127+ memory T cell subset and decreased naïve T cells, which was not recovered within 9 – 11 months post-surgery. Although NK cells showed an activated phenotype, they were numerically lower in patients with morbid obesity when compared to healthy controls. The NK cell population further decreased after surgery and did not recover quantitatively within the study period. Conclusions Our results clearly demonstrate that the rapid adaptions in inflammatory parameters and adipocytokine levels that occur within the first year post-surgery do not translate to the peripheral immune cells. Apart from that, we described highly affected, distinct immune cell subsets, defined as CD127+ memory T cells and monocytic CD14+, HLA-DR, CD11b+, CXCR3+ cells, that might play a significant role in understanding and further decoding the etiopathogenesis of morbid obesity.